2020
DOI: 10.1111/jdv.16248
|View full text |Cite
|
Sign up to set email alerts
|

Reflectance confocal microscopy diagnostic accuracy for malignant melanoma in different clinical settings: systematic review and meta‐analysis

Abstract: Background The diagnostic accuracy of reflectance confocal microscopy (RCM) of cutaneous malignant melanoma (MM) seems promising. However, clinical scenarios in which RCM is most useful are still to be established. Objectives To assess the diagnostic accuracy of RCM for MM diagnosis according to study design, lesion type and diagnostic modality. Secondary outcomes include a comparison with dermoscopy. Methods A systematic literature search was conducted on PubMed, Embase, Scopus and Cochrane Public Library Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 53 publications
(276 reference statements)
0
30
0
3
Order By: Relevance
“…A more recent and larger systematic review of 7352 lesions reported a pooled sensitivity of 92% and specificity of 70% for the diagnosis of melanoma [25]. In the study, the diagnostic accuracy of RCM remained high regardless of the lesion type [25]. RCM was shown to be useful for the detection of amelanotic melanoma with poor dermoscopic features [26,27].…”
Section: Melanomamentioning
confidence: 78%
See 1 more Smart Citation
“…A more recent and larger systematic review of 7352 lesions reported a pooled sensitivity of 92% and specificity of 70% for the diagnosis of melanoma [25]. In the study, the diagnostic accuracy of RCM remained high regardless of the lesion type [25]. RCM was shown to be useful for the detection of amelanotic melanoma with poor dermoscopic features [26,27].…”
Section: Melanomamentioning
confidence: 78%
“…A systematic review of 909 lesions reported that RCM had a sensitivity of 93% and specificity of 76% for the diagnosis of melanoma [24]. A more recent and larger systematic review of 7352 lesions reported a pooled sensitivity of 92% and specificity of 70% for the diagnosis of melanoma [25]. In the study, the diagnostic accuracy of RCM remained high regardless of the lesion type [25].…”
Section: Melanomamentioning
confidence: 80%
“…RCM is widely used for melanoma non-melanoma skin cancer diagnostics [ 34 , 35 , 36 , 37 ] and treatment management [ 38 , 39 ]. RCM as an optical biopsy method is also used for inflammatory skin diseases diagnostics and treatment monitoring [ 23 , 24 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the past few years, reflectance confocal microscopy (RCM) has been employed as a noninvasive technique to visualize the skin at quasi-histological resolution; it has also been used as an add-on tool in the diagnosis of skin cancer, as a second level of examination after dermoscopy, to improve diagnostic accuracy [9][10][11][12]. Additionally, due to the fact that RCM avoids skin biopsy, it has also been applied to the investigation of skin aging signs [13].…”
Section: Introductionmentioning
confidence: 99%